The Shisong Cardiac Center in Cameroon: An Example of a Long-Term Collaboration/Cooperation Toward Autonomy - Giamberti, Alessandro; Butera, Gianfranco; MVE Mvondo, Charles; Cirri, Silvia; Varrica, Alessandro; Moussaidi, Nadia; Isgrò, Giuseppe; Ambassa, Jean Claude; Tantchou, Cabral; Giamberti, Giovanni; Frigiola, Alessandro (Frontiers in Pediatrics, 2018)
Congenital heart diseases (CHD) are present in nearly 1% of live births; according to WHO, there are 1.5 million newborns affected by CHD per year and more than 4 million children waiting for cardiac surgery treatment worldwide. The majority of these children (approximately 90%) could be treated, saved and subsequently have a good quality of life but unfortunately, in developing countries with a suboptimal care or no access to care, they are destined to die. Cameroon, one of the 40 poorest countries in the world, is a typical example of this dramatic scenario and this is why we started a collaboration project with a local religious partner (Tertiary Sisters of Saint Francis) in 2001 with the aim of establishing the first cardiac surgery center in this country. There are various well-known organizational models to start a cooperation project in pediatric cardiac surgery in a developing country. In our case, the project included a long-term collaboration with a stable local partner, a big financial investment and a long period of development (10 years or more). It is probably the most difficult model but it is the only one with the greatest guarantee of success in terms of sustainability and autonomy. The aim of this study is to analyze the constructive and problematic aspects of the 17-year collaboration in this project, and to assess possible solutions regarding its critical issues. Although much has been done during this 17-year we are aware that there is still a lot that needs to be done.